Diseño e implementación de una notificación sanitaria en la microempresa APHI helados - Álvarez Tovar, Paola Stefania (2019)
This present project has as objective implement a health notification in APHI ICE CREAM microenterprise, since it will help to improve products quality, increase sales and new market places. For this, a diagnostic was made, which identified that elaborated product complies in large part with the regulations, that is the reason, the necessity of implementing health notification before mentioned. The process was the following: Obtain the IRS activity (Internal Revenue Service) in this case the company gets the SETR (Simplified Ecuadorian Tax Regimen) to attain the categorization of the company which was constituted as a microenterprise, access the operating licence, carry out physicochemical analysis, microbiological, instrumental, nutritional; verifying that obtained results in the analysis are in concordance with current regulations, the label and labeling was designed, a certificate of the container specification was taken, the declaration of the batch code was made, then the product elaboration was briefly described with its flow diagram, in order to achieve with implementation, a payment order was issued for a health notification fee and finally it was obtained. With implementation of health notification, it is possible to improve the quality standards, safety, personal hygiene, cleaning and disinfection of facilities, individual security; which tends to improve the quality and safety of the product and the economic income of the company.